Neuroprotective Role of Ranolazine in Parkinson Disease: Drosophila Melanogaster Model - Parvesh,; Kumar, Sandeep; Singh, Govind; Khatri, Ramchander; Shukla, Sunil; Kaushik, Kamal; Lather, Amit; Hooda, Tanuj (Scripta Medica, 2025)
Background/Aim: Among the neurological ailments, Parkinson disease (PD) might be one of the most mysterious and intricate ones. The brain produces less dopamine as PD worsens, making it harder for a person to control their movements. In literature the effect of ranolazine (Rn) in the CNS has been proposed for the management of pain and epilepsy. So, it was hypothesised that ranolazine could act in neuroprotection. Aim of this study was to explore ranolazine effect in Parkinson and neuronal cells. Methods: Drosophila melanogaster has been employed. Five groups, each with 100 flies were: Group 1: control; Group 2: vehicle treated; Group 3: PD + ranolazine treated (1 mg/mL); Group 4: PD + ranolazine treated (2 mg/mL); Group-5: PD + ranolazine treated (4 mg/mL). PD was induced by paraquat. Part A involved the estimation of mortality index at 2-6 h. Estimation of climbing assay at 2 h, 4 h and 6 h and biochemical parameters such as oxidative stress were performed at 6 h.Results: At different concentration of ranolazine percentage climbing of flies was found improved. Ranolazine at dose of 4 mg/mL showed significant reduction in percentage mortality at 24 h. Ranolazine at dose of 4 mg/mL showed a significant effect on total protein content level. Ranolazine 1 mg/mL showed significant effect and 2 mg/mL showed significant reduction in superoxide dismutase (SOD) level as compared to vehicle group. Ranolazine 1 mg/mL, 2 mg/mL and 4 mg/mL showed significant reduction in malondialdehyde (MDA) level as compared to vehicle group. Conclusion: The present findings suggest that ranolazine has a good neuroprotective potential in the treatment of PD in flies. Further studies still required to be performed so as to explore its potential in clinical trials.